HUMIC/FULVIC ACID AND NITROGEN IN THE CORN CROP YIELD - Batista, V.V.; Adami, P.F.; Ferreira, M.L.; Giacomel, C.L.; Silva, J.S.; Oligini, K.F. (Revista Brasileira de Engenharia de Biossistemas, 2018)
Corn has great importance to the world economy and due to it, alternatives to increase yield are continuously evaluated. The objective of this study was to evaluate corn crop development and its yield under different treatments with isolated and/or associated use of nitrogen and humic/fulvic acids. The study was carried out at the Universidade Tecnológica Federal do Paraná, Dois Vizinhos, PR, during the 2017/2018 growing season. As source of nitrogen was used urea and humic/fulvic acids as a commercial product (biostimulant). A randomized complete block design with seven treatments and four replicates was used: 1: application of ½ dose of biostimulant in V4 + application of ½ dose in V8; 2: application of full dose of the biostimulant in V4; 3: application of full dose of the biostimulant in V4; 4: nitrogen; 5: nitrogen + application of full dose of the biostimulant in V8; 6: nitrogen + full dose of the biostimulant in V4; 7: without nitrogen and without biostimulant (control). Acids were applied via leaf and nitrogen (N) (170 Kg ha-1) in sidedress at corn V4. Corn morphological traits, yield components and final yield were evaluated at the end of the crop cycle. Data were submitted to analysis of variance and when significance was found, Scott-Knott test was applied at a 5% probability. The use of humic/fulvic acids did not interfere in the morphological traits of corn plants, nor on the yield components and final yield, either alone or associated with N. Uréia N provides an increase in the number of grains per row and grains per spike, thousand grains weight and yield per spike and per area.